APLIKASI PENGENALAN PAHLAWAN NASIONAL DAN PAHLAWAN REVOLUSI BERBASIS ANDROID - Jodi Hendrawan; Ika Devi Perwitasari ((JurTI) Jurnal Teknologi Informasi, 2019)
Abstract - Heroes of revolution are titles or titles given to military officers who died in the betrayal tragedy of the G30S / PKI Indonesian Communist Party (PKI) which took place in Jakarta and Yogyakarta on September 30, 1965. National heroes are titles given to Indonesian citizens who fighting against occupation that had fallen in the battlefield. So that during his lifetime he left behind achievements or progress for the Republic of Indonesia. Where currently there is minimal knowledge of students or students regarding hero figures and lack of media for the introduction of heroes in Indonesia. With this, the application of national hero recognition and android-based revolution heroes is designed. So that it can increase the knowledge and interests of students or students and increase their sense of nationalism. System development is carried out with the watefall model and uses the concept of object-oriented development, OOP (Object Oriented Programming) and uses the UML modeling process (Unified Modeling Language) for the development of national recognition applications and android-based revolution heroes.Keywords - Android, Applications, UML, OOP, Heroes. Abstrak - Pahlawan revolusi merupakan gelar atau sebutan yang diberikan kepada perwira militer yang gugur dalam tragedi pengkhianatan Partai Komunis Indonesia (PKI) G30S/PKI yang terjadi di Jakarta dan Yogyakarta pada tanggal 30 September 1965. Pahlawan nasional adalah gelar yang diberikan kepada warga negara Indonesia yang berjuang melawan penjajahan yang telah gugur dimedan peperangan. Sehingga semasa hidupnya meninggalkan prestasi atau kemajuan untuk Negara Republik Indonesia. Dimana saat ini minim sekali pengetahuan siswa/i atau pelajar mengenai tokoh-tokoh pahlawan serta kurangnya media untuk pengenalan para pahlawan di Indonesia. Dengan adanya hal ini maka dilakukan perancangan aplikasi pengenalan pahlawan nasional dan pahlawan revolusi berbasis android. Sehingga dapat meningkatkan pengetahuan dan minat siswa/i atau pelajar serta menigkatkan rasa nasionalisme. Pengembangan sistem dilakukan dengan model watefall dan menggunakan konsep pengembangan berorientasi objek, OOP  (Object Oriented Programming) serta menggunakan proses pemodelan UML (Unified Modeling Language) untuk pengembangan aplikasi pengenalan pahlawannasional dan pahlawan revolusi berbasis android.Keywords - Android,Aplikasi, UML, OOP, Pahlawan.